2005
DOI: 10.1016/j.ymthe.2005.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Encapsidation of Prokaryotic Sequences during Recombinant Adeno-Associated Virus Production and Their in Vivo Persistence after Vector Delivery

Abstract: Recombinant adeno-associated virus vectors (rAAV) have been successfully used for long-term gene expression in animal models and in patients. However, while the therapeutic potential of rAAV appears promising, safety issues, including contaminants found in vector stocks, must be further evaluated. We previously reported that a cis-acting replication element present within the AAV-2 p5 promoter was responsible for the encapsidation of rep-cap sequences observed during rAAV production. In that study, we also not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 33 publications
3
92
1
Order By: Relevance
“…81 The inability to recapitulate the human findings in an animal model led to ongoing controversy about the pathophysiological basis of the transaminase elevation and loss of F.IX expression, 82 and multiple alternative hypotheses were advanced (Table 2). [83][84][85][86][87][88] However, if the observed toxicity was indeed related to the catabolism of the capsid, then this aspect of drug metabolism needed to be understood in greater detail. Early studies by Engelhardt and colleagues 89,90 showed that AAV vector particles are indeed ubiquitinated once internalized in the cytosol, a step that is fundamental for targeting intracellular proteins for degradation through This approach has been shown to be effective in some instances.…”
Section: Immune Responses In Aav Gene Therapy 25mentioning
confidence: 99%
“…81 The inability to recapitulate the human findings in an animal model led to ongoing controversy about the pathophysiological basis of the transaminase elevation and loss of F.IX expression, 82 and multiple alternative hypotheses were advanced (Table 2). [83][84][85][86][87][88] However, if the observed toxicity was indeed related to the catabolism of the capsid, then this aspect of drug metabolism needed to be understood in greater detail. Early studies by Engelhardt and colleagues 89,90 showed that AAV vector particles are indeed ubiquitinated once internalized in the cytosol, a step that is fundamental for targeting intracellular proteins for degradation through This approach has been shown to be effective in some instances.…”
Section: Immune Responses In Aav Gene Therapy 25mentioning
confidence: 99%
“…7,8 To determine whether such undesirable packaging of non-transgene DNA sequences might be reduced during rHSV-based rAAV production, two lots of rAAV1 vector expressing the human a-1 antitrypsin (rAAV1-CB-hAAT) generated and purified as described in Materials and Methods were subjected to an extensive nuclease treatment to remove any nonencapsidated nucleic acid impurities, and assessed for the presence of particles containing HSV DNA by a real-time quantitative PCR (qPCR) assay targeted to the HSV UL36 gene sequence. The HSV UL36 sequence was found to be packaged at 0.0076-0.0094% of the total rAAV vg, accounting for 6.4-7.8 ng of total HSV DNA per 1Â10 12 rAAV vg ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9] Using an rHSV-based method to produce rAAV1-CB-hAAT vectors, we found that residual HSV DNA sequences were randomly packaged, and the average HSV DNA sequence copy numbers detected were approximately 0.012% of the total rAAV vg, corresponding to approximately 10 ng of total HSV DNA per 1Â10 12 vg of rAAV. This is at least 100-fold less than the level of residual plasmid DNA (1.2-6.3% of the total rAAV vg) reported by Chadeuf et al, 8 and, when expressed as ng of residual DNA per 1Â10 12 vg of rAAV, is comparable with the lowest amount of residual plasmid DNA reported by Hauck et al 9 (10 ng vs 8.6 ng). The encapsidated residual HSV DNA sequences are most likely single-stranded DNA based on the observations from Southern blot analysis of DNA transferred under neutral conditions, although we could not completely exclude the possibility that part of the encapsidated HSV DNA are double stranded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations